The Influence of Social Environment, Religiosity, and Customer Knowledge on Saving Decisions with Wadi'ah Contracts at Bank Muamalat Indonesia Tulungagung Sub-Branch - Harisah Al-islam; Syafrudin Arif Marah Manunggal (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
This paper aims to examine the effect of the social environment, religiosity, and customer knowledge partially and simultaneously on the decision to save with a wadi'ah contract at Bank Muamalat Indonesia Tulungagung Sub-Branch. The research method used is quantitative method. This research is sourced from primary data generated from the distribution of questionnaires. The statistical test used is the classical assumption test and multiple linear regression analysis. The results of this study are the social environment partially influences the decision to save with a wadi'ah contract at Bank Muamalat Indonesia Tulungagung Sub-Branch. Religiosity does not partially affect the decision to save with a wadi'ah contract at Bank Muamalat Indonesia Tulungagung Sub-Branch. Customer knowledge partially influences the decision to save with a wadi'ah contract at Bank Muamalat Indonesia Tulungagung Sub-Branch. The variables of social environment, religiosity, and customer knowledge simultaneously have an effect of 61.4% on the variable of saving decisions with wadi'ah contracts at Bank Muamalat Indonesia Tulungagung Sub-Branch. While the remaining 38.6% is influenced by other variables outside of this model.